Polarity-Sensitive Coumarins Tailored to Live Cell Imaging. - Signore, Giovanni; Nifosì, Riccardo; AIbertazzi, Lorenzo; Storti, Barbara; Bizzarri, Ranieri (Journal of the American Chemical Society, 2010)
Polarity-dependent fluorescent probes are recently attracting interest for high-resolution cell imaging. Following a stepwise rational approach, we prepared and tested a toolbox of new coumarin derivatives tailored to in vivo imaging applications. Our compounds are characterized by a donor-(coumarin core)-acceptor molecular structure, where the electron donor is represented by alkylether or naphthyl groups, and the electron acceptor is represented by benzothiazene and cyano groups. Prior to synthesis, the substitution patterns were screened by computational methods to provide functional fluorescent derivatives easy to synthesize, and with excitation in the visible region of spectrum. We set up a robust synthetic procedure tunable on the substitution patterns to achieve. These coumarins possess excellent fluorescence quantum yields (up to 0.95), high molar extinction coefficients (up to 46,000 M cm), and large Stokes shifts. Furthermore, they display strong solvatochromism, being almost non-emissive in water and very fluorescent in less polar media (up to 780-fold enhancement in brightness). The solvatochromism of these compounds can be accounted for by a photophysical method encompassing two communicating excited states. When tested on cultured cells, the results showed that the developed coumarins were not harmful and their photophysical properties were unchanged compared to free solution. According to the determined solvatochromic properties, the coumarin fluorescence was detected only in the most lipophilic environments of the cell. The prepared compounds represent remarkable tools to investigate subtle biochemical processes in the cell environment after appropriate conjugation to biomolecules, and at the same time constitute the basis for further engineering of a new generation of biosensors.